Life‐cycle reliability‐based robust design optimization for GP model with response uncertainty. (19th March 2021) - Feng, Zebiao; Wang, Jianjun; Ma, Yizhong; Yang, Guikang
Abstract: Reliability‐based robust design optimization (RBRDO) is a crucial tool for life‐cycle quality improvement. Gaussian process (GP) model is an effective alternative modeling technique that is widely used in robust parameter design. However, there are few studies to deal with reliability‐based design problems by using GP model. This article proposes a novel life‐cycle RBRDO approach concerning response uncertainty under the framework of GP modeling technique. First, the hyperparameters of GP model are estimated by using the Gibbs sampling procedure. Second, the expected partial derivative expression is derived based on GP modeling technique. Moreover, a novel failure risk cost function is constructed to assess the life‐cycle reliability. Then, the quality loss function and confidence interval are constructed by simulated outputs to evaluate the robustness of optimal settings and response uncertainty, respectively. Finally, an optimization model integrating failure risk cost function, quality loss function, and confidence interval analysis approach is constructed to find reasonable optimal input settings. Two case studies are given to illustrate the performance of the proposed approach. The results show that the proposed approach can make better trade‐offs between the quality characteristics and reliability requirements by considering response uncertainty.